YouTube-Based Instructional for Quality and Inclusive CAD Patternmaking Learning: Effects on Student Engagement, Cognitive Load, and Learning Achievement - Weni Nelmira; Rima Agustia Utami; Reni Fitria (Postgraduate, University of Mataram, 2026)
The use of YouTube-based learning has become increasingly relevant in vocational education, particularly in technical and procedural courses such as CAD Patternmaking. This study aims to analyze the contribution of YouTube-based learning to student engagement, cognitive load, and learning achievement in a CAD Patternmaking course. A quantitative approach with an ex post facto design was employed. The sample consisted of 107 Fashion Design students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression and stepwise multiple regression with SPSS. The results show that YouTube-based learning contributes positively and significantly to student engagement and negatively and significantly to cognitive load. In addition, YouTube-based learning and student engagement simultaneously contribute significantly to learning achievement, while cognitive load does not have a significant partial contribution. These findings indicate that learning achievement in YouTube-based CAD Patternmaking learning is more strongly influenced by student engagement than by perceived cognitive load. In conclusion, YouTube-based learning can effectively support vocational learning outcomes when designed to enhance student engagement. This study provides practical implications for developing structured video-based learning strategies in vocational education.